Alterations in nutritional status and metabolic profile of women before and after roux-en-y gastric bypass weight-loss surgery - Borges, Thawana de Oliveira (2016)
Obesity is a serious public health problem and is associated with several comorbidities. Studies show that bariatric surgery is the most effective treatment for morbid obesity (morbid). The objective of this study was toevaluate the nutritional status and metabolic profile of women after Roux-en-y gastric bypass weight-loss surgery (RYGBP). Retrospective and analytical study in private clinical specializing in obesity surgery in Brasilia-DF. The sample consisted of 54 obese women, with a mean age of 41 years submitted to RYGBP from 2 to 5 years. We collected anthropometric variables: height, preoperative weight, body mass index -preoperative BMI, current weight, current BMI, % loss of excess weight (EWL%) and ideal weight. And biochemical variables: erythrogram, iron deficiency anemia markers, ionized calcium, parathyroid hormone, D, B1, B6, B9 and B12 vitamins, fasting blood glucose, glycated hemoglobin and lipid profile, collected in the first and last postoperative examination. Observed a significant reduction in weight and BMI, but with greater EWL% in the first two years, and reduced levels of triglycerides, VLDL, ferritin, hematocrit, glycated hemoglobin, vitamin D and significant increase of iron, total iron-bindingcapacity, HDL, folic acid and vitamin B6. The results indicate that bariatric surgery improves the nutritional status and metabolic profile in women submitted RYGBP between two and five years of surgery.